2022
DOI: 10.3389/fmolb.2022.1023381
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of silk genes in Ephestia kuehniella and Galleria mellonella revealed duplication of sericin genes and highly divergent sequences encoding fibroin heavy chains

Abstract: Silk is a secretory product of numerous arthropods with remarkable mechanical properties. In this work, we present the complete sequences of the putative major silk proteins of E. kuehniella and compare them with those of G. mellonella, which belongs to the same moth family Pyralidae. To identify the silk genes of both species, we combined proteomic analysis of cocoon silk with a homology search in transcriptomes and genomic sequences to complement the information on both species. We analyzed structure of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…A previous study on the pyralid moths G. mellonella and E. kuehniella showed that the known sericin genes, with the exception of P150/ser6, lie within the cluster of orthologous genes in the corresponding chromosomal regions [14]. Such microsynteny can be also observed between B. mori and G. mellonella or E. kuehniella (Fig 5).…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…A previous study on the pyralid moths G. mellonella and E. kuehniella showed that the known sericin genes, with the exception of P150/ser6, lie within the cluster of orthologous genes in the corresponding chromosomal regions [14]. Such microsynteny can be also observed between B. mori and G. mellonella or E. kuehniella (Fig 5).…”
Section: Resultsmentioning
confidence: 67%
“…Such microsynteny can be also observed between B. mori and G. mellonella or E. kuehniella (Fig 5). The results also show a number of local rearrangements and duplications in this region including the expansion of several sericin genes in G. mellonella compared to related moths [14].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations